Grzyby towarzyszące ryzomorfom Armillaria spp. na Populus tremula L. - Damszel, Marta; Dyczewska, Katarzyna; Mastalerz, Jędrzej; Przemieniecki, Sebastian (Leśne Prace Badawcze, 2020)
The economic significance of aspen Populus tremula L. is only marginal, which is the main reason for its low share in the structure of stands. However, aspen can play a decisive ecological role as a pioneer tree in the succession of forest communities and may decrease the occurrence of pathogenic fungi. Aspen is also dying out and in order to determine possible biotic causes, we examined taxa of fungi using classical and molecular methods in the area of the Czerwony Dwór Forest District, Subdistrict Rogale, compartments 74b and 75j. The health of aspen trees and the quantitative and qualitative structure of microorganisms associated with Armillaria spp. was evaluated. Based on our health assessment of the aspen, we conclude that the main reason for its dying out is the intensification of root rot, which is a result of Armillaria spp weakening the trees. In the general pool of Armillaria -associated microorganisms, saprotrophs were dominating, and the fungus Fomitopsis pinicola commonly inhabited the poplar stems, whereas pathogen antagonists comprised the lowest proportion. In the quantitative and qualitative structure of fungi found in rhizomorphs, the composition of ecological groups inhabiting stumps was found to be favourable nevertheless. The increasing frequency of pathogens on the logs is a major premise for removing trees affected by Armillaria , because aspen stumps are a good food base for A. cepistipes and A. ostoyae which ultimately spread within the stand. Treatment of stumps with preparations stimulating the decomposition of wood is not recommended for logs that form the food base for pathogenic fungi.